Humanistic burden of patients with chronic graft-versus-host disease - systematic literature review of health-related quality of life and functional status. Issue 5 (4th May 2019) - Agh, Tamas; Csanadi, Marcell; Voko, Zoltan; Webb, Thomas; Jeyakumaran, Dusha; Trudeau, Jeremiah; Sengupta, Nishan; Schain, Frida; Mattsson, Jonas
ABSTRACT: Introduction : Chronic graft-versus-host disease (GVHD) is a serious complication of allogeneic hematopoietic stem cell transplantation (HSCT). This study aims to provide a systematic overview of evidence on the health-related quality of life (HRQoL) and functional capacity of HSCT patients with National Institutes of Health (NIH)-defined chronic GVHD. Areas covered : English-language articles published between 2007 and 2017 were searched using PubMed. Studies that used the 2005 or 2015 NIH consensus criteria for the diagnosis and staging of chronic GVHD and had a cohort size of at least 100 patients were included. Expert opinion : Disease severity and organ involvement were the most important predictors of HRQoL and functionality in chronic GVHD patients. Further, identified predictors of HRQoL were nutrition status and functional capacity, while functional status was also associated with disease symptoms, nutrition status, age, and survival. Data regarding the effect of symptom bother on HRQoL were limited. Our findings confirm that the management of chronic GVHD should focus on improving not only clinical outcomes but also on HRQoL and functional capacity. Therefore, to evaluate new treatment options it is recommended to include patient relevant endpoints into prospective studies. This study also highlights the importance of nonpharmacological aspects in the management of chronic GVHD.